Past, Current, and Future of Immunotherapies for Prostate Cancer - Boettcher, Adeline N.; Usman, Ahmed; Morgans, Alicia; VanderWeele, David J.; Sosman, Jeffrey; Wu, Jennifer D. (Frontiers in Oncology, 2019)
Prostate cancer (PCa) is the most common cancer in men, and the second leading cause of cancer related death in men in Western countries. The standard therapy for metastatic PCa is androgen suppression therapy (AST). Men undergoing AST eventually develop metastatic castration-resistant prostate cancer (mCRPC), of which there are limited treatment options available. Immunotherapy has presented substantial benefits for many types of cancer, but only a marginal benefit for mCRPC, at least in part, due to the immunosuppressive tumor microenvironment (TME). Current clinical trials are investigating monotherapies or combination therapies involving adoptive cellular therapy, viral, DNA vaccines, oncolytic viruses and immune checkpoint inhibitors (ICI). Immunotherapies are also being combined with chemotherapy, radiation, and AST. Additionally, preclinical investigations show promise with the recent description of alternative ways to circumvent the immunosuppressive nature of the prostate tumor microenvironment, including harnessing the immune stimulatory NKG2D pathway, inhibiting myeloid derived suppressor cells, and immunomodulatory oncolytic viruses. Herein we provide an overview of recent preclinical and clinical developments in cancer immunotherapies and discuss the perspectives for future immunotherapies in PCa.